Bilateral Iris Mammillations in Amblyopic Eyes without Oculodermal Melanocytosis or Neurofibromatosis - Megumi Yamamoto; Tatsuya Mimura; Koichi Matsumoto; Shigeki Hamano; Hisataka Nanba; Shoko Ubukata; Emiko Watanabe; Atsushi Mizota (Case Reports in Ophthalmological Medicine)
Purpose. Iris mammillations are related to oculodermal melanosis and iris nevi. We report a rare case of bilateral simple iris mammillations without ocular melanosis or systemic neuronal disorders. Case Report. A healthy 10-year-old Japanese girl was found incidentally to have bilateral iris mammillations while being treated for amblyopia. The best-corrected visual acuity was 20/40 in both eyes. Ocular examination showed evenly spaced, uniform-size, iris protrusions completely covering the iris surface bilaterally. There were no other ocular or neurological abnormalities. Conclusion. To the best of our knowledge, this is the first report of bilateral iris mammillations in Japan. Our case emphasizes that iris mammillations can occur even without ocular melanocytosis or systemic diseases.